Compact omni‐directional circularly polarised antenna utilising bended dipoles and integrated baluns. Issue 10 (13th July 2017) - Yu, Yufeng; Xiong, Jiang; Li, Hui
Abstract : A circular‐polarised antenna with omni‐directional radiation is presented in this study. The proposed antenna consists of four bended dipoles, excited simultaneously by integrated baluns. The Eφ and Eθ components, generated by the horizontal and vertical parts of the bended dipoles, are shown to have a phase difference of 90°. The operating principle of achieving circular polarisation (CP) with bended dipoles are described and derived, according to which guidelines for designing CP antennas are provided. Following the guidelines, a prototype of the compact omni‐directional CP antenna is fabricated, with a size of 0.27 λ 0  × 0.27 λ 0  × 0.13 λ 0, a fractional bandwidth of 9% at 2.43 GHz and an average left‐handed circular polarisation (LHCP) gain above 0.15 dBic in the operating band.